Sb2S3/Sb2Se3-based high-performance self-power broadband photodetector - Pukhraj Prajapat; Pargam Vashishtha; Preeti Goswami; Vaibhav Kandwal; Lalit Goswami; Anuj Sharma; Aditya Yadav; Preetam Singh; Govind Gupta (Next Materials)
The field of broadband photodetectors has significantly benefited from the development of self-powered devices, which have a wide range of applications in various sectors, including industrial security, satellite communication, image sensing, environmental monitoring, etc. This article describes the growth and fabrication of a Sb2S3/Sb2Se3 heterostructure-based optoelectronic device. The advantageous properties of heterostructure demonstrate a combined effect of Sb2Se3 and Sb2S3 materials, like the band alignment and a wide detection range from ultraviolet to near-infrared with exceptional self-powered photodetection performance. The band alignment feature is vital in applications where photo response is critical to the function of the device, such as solar cells or photodetectors. The constructed heterostructure device exhibits figure-of-merits including responsivity, NEP, and detectivity under the illumination of 1064 nm, are found to be 3.45 mAW−1, 2.08×10−12 WHz−1/2, and 1.44×1010 Jones, respectively. These results could pave the way for even more efficient and reliable photodetectors, making them an essential tool for various critical applications.